2016
DOI: 10.1111/mpp.12332
|View full text |Cite
|
Sign up to set email alerts
|

Leptosphaeria maculans effector AvrLm4‐7 affects salicylic acid (SA) and ethylene (ET) signalling and hydrogen peroxide (H2O2) accumulation in Brassica napus

Abstract: To achieve host colonization, successful pathogens need to overcome plant basal defences. For this, (hemi)biotrophic pathogens secrete effectors that interfere with a range of physiological processes of the host plant. AvrLm4-7 is one of the cloned effectors from the hemibiotrophic fungus Leptosphaeria maculans 'brassicaceae' infecting mainly oilseed rape (Brassica napus). Although its mode of action is still unknown, AvrLm4-7 is strongly involved in L. maculans virulence. Here, we investigated the effect of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…Thus, we hypothesize that AvrLm1 as a virulence factor facilitates the phosphorylation of BnMPK9, leading to the suppression of SA-dependent pathway and supporting the colonization of L. maculans at the initial infection stage. AvrLm4-7, another L. maculans effector, was recently reported to act as a virulence factor by suppressing the host SA signaling pathway ( Nováková et al., 2016 ). AvrLm1 and AvrLm4-7 also contribute to the aggressiveness of L. maculans during leaf infection ( Huang et al., 2006 , Huang et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize that AvrLm1 as a virulence factor facilitates the phosphorylation of BnMPK9, leading to the suppression of SA-dependent pathway and supporting the colonization of L. maculans at the initial infection stage. AvrLm4-7, another L. maculans effector, was recently reported to act as a virulence factor by suppressing the host SA signaling pathway ( Nováková et al., 2016 ). AvrLm1 and AvrLm4-7 also contribute to the aggressiveness of L. maculans during leaf infection ( Huang et al., 2006 , Huang et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…; Nováková et al . ), a role in fungal fitness. Indeed, AvrLm3 was shown to be among the 10 most highly expressed L. maculans genes during the first stages of plant infection, even in isolates displaying a virulent phenotype due to the masking effect of AvrLm4‐7 (Plissonneau et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nováková et al . () showed that the complementation of isolate Nz‐T4, in which AvrLm4‐7 was highly RIPed, with an avirulent allele of AvrLm4‐7 , resulted in significantly larger leaf lesions on susceptible cultivars compared to noncomplemented controls. Huang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the up-regulation of HR-related genes characterized by signaling hormones (Chu et al, 2014 ; Nováková et al, 2016b ; Uloth et al, 2016 ), regulatory genes such as the transcription factors WRKY (Zhou et al, 1997 ) and calmodulin-binding transcription activator (CAMTA) (Rahman H. et al, 2016 ) have also been implicated to regulate the disease response in Brassica pathosystems (Zhou et al, 1997 ). The WRKY gene was studied in B. napus - S. sclerotiorum and - Alternaria brassicae pathosystems, where gene expression was increased upon pathogen infection alongside defense-related hormones (Yang et al, 2009 ; Zhao et al, 2009 ).…”
Section: Strategiesmentioning
confidence: 99%